Production of organic manure fertilizer in Padukuhan Donoasih, Sleman - Lis Noer Aini; Tri Hartanto; Eko Hanudin; Yuanita Yuanita (Universitas Muhammadiyah Magelang, 2022)
Donoasih is one of the hamlets in Donokerto Turi which is located on the southern slope of Mount Merapi. The people in this hamlet have various social conditions, both education and profession. Most of the community in this village are farmers and ranchers. The problem in this village is the management of livestock manure that has not been optimal. Some livestock manure and agricultural waste are left in the hope that they will decompose on their own. In order to overcome these problems, it is necessary to increase understanding of community about the utilization of livestock manure into more useful products. The solution offered is counseling and assistance in processing animal manure into fertilizer so that it can provide better benefits. The results obtained showed that after the activity was carried out, 100% of the farming-breeding communities in the Donoasih village could make organic fertilizers, both solid organic fertilizers and liquid organic fertilizers derived from livestock manure and agricultural waste.